The Use oh Metaphor as an Expression of Emotion in Song Lyrics “Ah” by Nadin Amizah - Rima Listiawati; Titik Sudiatmi; Sri Muryati (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Metaphors have played an important role in providing emotions in song lyrics, but the use of metaphors as a means of self-actualization of emotional expression in popular music is still small. The research “The Use of Metaphor as an Expression of Emotion in Nadin Amizah's Song Lyrics ‘Ah’” makes a unique contribution in highlighting the role of metaphor in building the emotional dimension of Indonesian popular music that has not received much attention in local studies. Most previous studies only focus on metaphors in poetry or prose and pay less attention to popular music genres. This research fills the void by analyzing how metaphors are used to express complex emotions, such as sadness and intimacy, in the song “Ah”, thus providing new insights into the interrelationship between language, music and emotional expression. This study aims to analyze the use of metaphors in the lyrics of the song “Ah” by Nadin Amizah as a means of emotional expression. The metaphors used are classified into three types, namely simple, implicit, and creative metaphors. Simple metaphors are language styles that are composed with straightforward sentence structures and vocabulary so that the meaning can be immediately understood without requiring in-depth interpretation, implicit metaphors are language styles that convey meaning indirectly through symbolism, connotation, or allusion, and creative metaphors are language styles that are innovative and not bound to certain patterns. It emphasizes creativity and originality in conveying ideas or messages. The analysis shows that the lyrics of this song express various emotions, such as happiness, gratitude, hope, and struggle. Simple metaphors are used to convey direct meaning, while implicit metaphors depict hidden meaning. Creative metaphors present unique and original imaginative expressions, reflecting the emotional journey from hardship to happiness. This research supports the theory that metaphors in Indonesian popular music play an important role in strengthening the relationship between songwriters and listeners and serve not only as an aesthetic element but also as an effective tool to create emotional resonance in listeners. In addition, these findings expand the understanding of how metaphors can be a means to communicate positive emotions in a musical context. It is hoped that this research can serve as a reference in the study of music language and literature, as well as encourage further exploration of the influence of metaphors in various genres of music on the emotional experience of listeners